The Role of Online Support Groups in Helping Individuals Affected by HIV and AIDS: Scoping Review of the Literature - Neil S Coulson; Heather Buchanan (JMIR Publications, 2022)
BackgroundOnline support groups provide opportunities for individuals affected by HIV and AIDS to seek information, advice, and support from peers. However, whether and how engagement with online support groups helps individuals affected by HIV and AIDS remains unclear, as does the nature of the evidence on this topic. ObjectiveThis scoping review sought to explore whether engagement with HIV and AIDS-related online support groups benefits members in terms of psychosocial well-being and illness management, whether members experienced any negative aspects of these groups, and what types of social support are exchanged within HIV and AIDS-related online support groups. MethodsA scoping review of English-language articles (including both qualitative and quantitative studies) was undertaken using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The databases searched included MEDLINE, PubMed, EMBASE, CINAHL, PsycINFO, CENTRAL (Cochrane Register of Controlled Trials), and Scopus. Key findings were synthesized using a narrative and thematic approach. ResultsA total of 22 papers met the inclusion criteria from an initial pool of 3332 abstracts. These papers included 23% (5/22) quantitative studies, 9% (2/22) mixed methods studies, and 68% (15/22) qualitative studies published between 2007 and 2019. Cross-sectional evidence suggests that engagement with HIV and AIDS-related online support groups is empowering for members and may lead to a range of psychosocial benefits. Furthermore, qualitative evidence suggests that these groups provide an opportunity to connect with similar people and share experiences. This can help improve self-worth, reduce stigma, facilitate improved illness management, and gain greater confidence when interacting with health professionals. However, online support groups are not without their limitations as qualitative evidence suggests that users may encounter examples of interpersonal conflict between members as well as be exposed to challenging content. Finally, HIV and AIDS-related online support groups are avenues through which individuals can solicit support, most commonly informational or emotional. ConclusionsHIV and AIDS-related online support groups may have some benefits for members, particularly in terms of providing social support. There is a need for a systematic review of this literature that includes an assessment of the methodological quality of the available evidence.